The Relationship Between Self-Efficacy, Duration of Hemodialysis, Therapy Adherence, and Quality of Life in Patients with Chronic Kidney Disease - Rhohimin Rhohimin; M Faizal; Rima Berti Angraini (Genius Journal, 2027)
Introduction : Chronic Kidney Disease (CKD) is a long-term illness with an increasing number of cases each year, including at Depati Bahrin Regional Hospital, which has recorded a rising trend of patients undergoing hemodialysis year after year. This condition has a significant impact on the physical, psychological, and social aspects of patients, thereby affecting their quality of life. Factors such as self- efficacy, duration of undergoing hemodialysis, and adherence to therapy play an important role in maintaining or improving the patients’ quality of life. Objective: This study aims to determine the relationship between self-efficacy, duration of undergoing hemodialysis, and adherence to hemodialysis therapy with the quality of life of chronic kidney failure patients in the Hemodialysis Unit of Depati Bahrin Regional Hospital, Bangka Regency Method: The study was conducted in July 2025 using a quantitative approach with a cross-sectional design. A total of 65 respondents were selected using purposive sampling. Data were collected using the CKD Self-Efficacy (CKD-SE) and KDQOL-SF questionnaires, then analyzed bivariately. Result: The results showed a significant relationship between self-efficacy (p=0.000), duration of hemodialysis (p=0.000), and adherence to therapy (p=0.039) with the patients’ quality of life. Patients with high self-efficacy, who had been undergoing hemodialysis for more than one year, and who adhered to the therapy tended to have a better quality of life. Conclusion: This study recommends that healthcare providers strengthen their educational role and psychosocial support to improve patients’ self-efficacy and adherence, thereby enhancing the quality of life of chronic kidney failure patients optimally.